2007
DOI: 10.1177/104063870701900120
|View full text |Cite
|
Sign up to set email alerts
|

Brain Lesions in Pigs Affected with Postweaning Multisystemic Wasting Syndrome

Abstract: Abstract. Anti-porcine circovirus type 2 (anti-PCV2) immunostaining was associated with cerebellar lymphohistiocytic vasculitis combined with hemorrhages (50 pigs) or with lymphohistiocytic meningitis (23 pigs) in pigs naturally affected with postweaning multisystemic wasting syndrome (PMWS). The animals originated from 12 farms in Rio Grande do Sul, Brazil. In total, 456 unthrifty 3-to 5-month-old postweaning pigs confirmed as PMWS cases were necropsied. Although most findings mimicked those extensively repor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

4
31
3

Year Published

2011
2011
2019
2019

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(38 citation statements)
references
References 18 publications
4
31
3
Order By: Relevance
“…In the present study, a 30 day-old piglet with splay legs revealed PCV2 antigen labeling in the endothelial cells of capillaries and degenerating neurons. These findings agree with reported observations of brain lesions and PCV2 antigen distribution in PMWS affected pigs in Brazil (Correa et al, 2007). Since some conflicting observations on the direct association of PCV2 with congenital tremors and ataxia in piglets have been reported (Kennedy et al, 2003;Stevenson et al, 2001), this aspect needs more in-depth investigation.…”
Section: Discussionsupporting
confidence: 65%
“…In the present study, a 30 day-old piglet with splay legs revealed PCV2 antigen labeling in the endothelial cells of capillaries and degenerating neurons. These findings agree with reported observations of brain lesions and PCV2 antigen distribution in PMWS affected pigs in Brazil (Correa et al, 2007). Since some conflicting observations on the direct association of PCV2 with congenital tremors and ataxia in piglets have been reported (Kennedy et al, 2003;Stevenson et al, 2001), this aspect needs more in-depth investigation.…”
Section: Discussionsupporting
confidence: 65%
“…4 However, no statistical analysis was performed in that study. The data from the current study support the hypothesis that blood vessels play a role in the pathogenesis of PCV2 infection of swine.…”
Section: Discussionmentioning
confidence: 99%
“…2,4,13,17,22,23 A marked increase in the incidence and severity of PCVAD was observed in eastern Canada in 2004 and was attributed to the emergence of the PCV2b virus cluster.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In this study, microscopic lesions were found only in the lungs, where multinucleated giant cells and prominent vascular lesions were detected first, with the parallel presence of nonsuppurative pneumonia. The presence of multinucleated giant cells in pig fetuses has so far been described only in the lymphoid organs (Opriessnig and Langohr, 2012) and vascular lesions have been reported only in growing and adult pigs with PMWS or PRDC (Opriessnig et al, 2006;Correa et al, 2007;Seeliger et al, 2007;Langohr et al, 2010;Szeredi et al, 2012;Resendes and Segalés, 2014). The presence of large amounts of PCV2 antigen in and around the blood vessels of different fetal organs suggests that the vascular system may be important in the pathogenesis of fetal PCV2 infection as well.…”
Section: Discussionmentioning
confidence: 99%